2015
DOI: 10.1371/journal.pone.0120680
|View full text |Cite
|
Sign up to set email alerts
|

Combining Microfluidics, Optogenetics and Calcium Imaging to Study Neuronal Communication In Vitro

Abstract: In this paper we report the combination of microfluidics, optogenetics and calcium imaging as a cheap and convenient platform to study synaptic communication between neuronal populations in vitro. We first show that Calcium Orange indicator is compatible in vitro with a commonly used Channelrhodopsine-2 (ChR2) variant, as standard calcium imaging conditions did not alter significantly the activity of transduced cultures of rodent primary neurons. A fast, robust and scalable process for micro-chip fabrication w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 50 publications
1
57
0
Order By: Relevance
“…1,5a) or suitable to be used for functional analysis using an inverted microscope. Previous studies have shown the ability of compartmentalized systems to record inter-chamber communication using calcium imaging 12,21 . While our system has the capacity for calcium imaging, we designed the system to have an large open well to allow for electrophysiology, which measures high temporal resolution (in millisecond scale) neuronal firing or synaptic transmission.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1,5a) or suitable to be used for functional analysis using an inverted microscope. Previous studies have shown the ability of compartmentalized systems to record inter-chamber communication using calcium imaging 12,21 . While our system has the capacity for calcium imaging, we designed the system to have an large open well to allow for electrophysiology, which measures high temporal resolution (in millisecond scale) neuronal firing or synaptic transmission.…”
Section: Resultsmentioning
confidence: 99%
“…These microfluidic devices have enabled studies of axonal injury 1517 , axon pathfinding 18 and cellular migration 19 . They have also been utilized to investigate synaptogenesis 20 and circuit connectivity 2124 . A compartmentalized model of synaptic competition has been devised allowing the study of differences in individual neurons by chemically treating one chamber and performing synapse counting in another 22 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The unique ability to study single cell signaling or small populations in microfluidics with be important in future understanding of cell heterogeneity, and it will have wide implications in many topics including cancer stem cells, metastasis, immunology, neuroscience, and more. Immunology has been one of the biggest directions for cell-cell communication and single cell analysis devices 34 , while neuroscience has been widely popular for long-distance communication 140142 . Despite this, there are still many unexplored biological areas where research could benefit from microfluidic cell-cell signaling devices.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…The device geometry helps in preventing the cross talk between neuronal populations. 14 Li et al 15 have exploited the use of microfluidic device for amperometric measurements of neurotransmitter release. The microscale environment of the device helps in the formation of in vitro neural networks between superior cervical ganglion and effector smooth muscle cells.…”
mentioning
confidence: 99%